Development of Tahfiz Teaching Materials In Improving Memory of The Al-Qur'an - Amin, Muhammad; Mardianto, Mardianto; Mahariah, Mahariah (Institut Agama Islam An-Nawawi Purworejo, 2025)
This study aims to develop a Juz Amma memorization teaching material that enhances students' Quran memorization skills at SMA IT Al-Fityah Binjai. The main focus is addressing the lack of adequate teaching materials for Quran memorization in the school. The development of this teaching material is expected to improve the quality of Quranic teaching and help students memorize more effectively. The study uses the Research and Development (R&D) method with the ADDIE model, consisting of five stages: Analyze, Design, Development, Implementation, and Evaluation. Data collection instruments include questionnaires, learning tests, and interviews. The study involved two subject matter experts and two media experts for material validation and was tested with class XI students enrolled in the tahfiz program. The results show that the subject matter validation received a score of 90% (